The need for psychological support for women waiting for gynaecological surgery - Łepecka-Klusek, Celina; Pilewska-Kozak, Anna B.; Syty, Kinga; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2010)
Aim: The aim of this study was to examine whether and what is the relationship between age of women and the need for emotional support while awaiting the scheduled gynaecological surgery. Material and methods : The study comprised 272 women who, within 2 months of 2008, underwent planned gynaecological surgeries in one of four selected hospitals in Lublin and Warsaw. The research tool was a questionnaire designed specifically for this study. The main study was preceded by a pilot study carried out among 25 women, the results of which were excluded from this study. Results : In nearly half (45.6%) of the respondents the suggestion of surgery induced negative feelings, such as fear, distrust and objections. Most women (72.8%) feared most the detection (or confirmation) of malignancy. Others were afraid of pain, complications, loss of femininity and/or fertility. Psychological support from the others was expected by 87.9% of respondents. The waiting time for surgery was adequate in the subjective assessment of the majority (79.0%). The division of women on grounds of age adopted in this study, differentiated significantly most of the studied characteristics of respondents, with the exception of demographic data. Conclusions : 1. Older women (> 49 years) more often than the younger (aged ≤ 49 years), feel fear of detection (or confirmation) of malignant neoplasm, find the waiting time for surgery appropriate and expect support primarily from medical staff. 2. Older women less likely than younger ones can expect – in their view – the assistance and support of families.